Hockey plays and strategies - Walter, Ryan; Johnston, Mike (Usa : Human Kinetics, 2010)
Authors Ryan Walter and Mike Johnston draw on their NHL coaching experience to pack Hockey Plays and Strategies full of offensive, defensive and special play systems proven to succeed in the fast-paced and agile style of hockey played today. They present detailed instruction for the specific skills, techniques, position responsibilities and team player requirements essential to the game with advice in sync with the major rule changes from 2004 which transformed game play.
includes bibliographical references and index.
Keywords: Hockey -- Offense; Hockey -- Coaching